MENINGKATKAN KETERAMPILAN BERBICARA MELALUI MODEL PEMBELAJARAN PAIRED STORY TELLING BERBANTUAN BONEKA TANGAN PADA SISWA KELAS III A SD - Sunarti dan Novita Retnanngrum (Universitas PGRI Yogyakarta, 2020)
Abstract The purpose of this study is to improve speaking skills trough a paired storytelling learning model assisted with hand puppets in3rd grade students Tegaldowo Elementary School. This research is a Classroom Action Research with steps from planning, implementing, observing, and reflecting which is carried out collaboratively between researchers and classroom teachers. The research subjects are3rd grade students consisting of 24 students. The data in the study were collected by observation, practice tests, documentation, and field notes. The instruments used are learning devices, observation sheets and tests. Speaking skills measured through this study include pronunciation, intonation, vocabulary, structure, and fluency in the analytical technique used is to calculate the average and calculate the percentage of completeness. The results of the study concluded that, the application of paired storytelling learning models assisted by hand puppets proved to be able to improve the speaking skills of 3rd gradestudents at Tegaldowo Elementary School. This can be proven by an increase in the speaking skills of students who have reached the Minimum Completion Criteria value, in the pre-cycle the average score of students is 60.41, with a completeness percentage of 20.83%. In the first cycle the average value of students was 70.42, with a percentage of completeness of 50%. In the second cycle the average value of students increased to 81.25, with a percentage of completeness 83.33%.Keywords :speaking skills, paired story telling with hand puppets.